Improving plasticity of metallic glass by electropulsing-assisted surface severe plastic deformation. (5th March 2019) - Ma, Chi; Suslov, Sergey; Ye, Chang; Dong, Yalin
Abstract: Using either electropulsing (EP) or surface severe plastic deformation (SSPD) to process metallic glasses can improve their plasticity, however, the moderate improvement in plasticity does not warrant a commercial usage. This work, for the first time, demonstrates the integration of electropulsing and surface severe plastic deformation is much more effective in improving the plasticity of metallic glasses than EP or SSPD treatment alone, opening a new avenue towards an unprecedented combination of strength and plasticity in metallic glasses. It is found that SSPD can generate microstructure heterogeneity featured by a mixture of matrix and plastically displaced regions with increased atomic volume. When applying EP and SSPD simultaneously, a synergistic effect occurs to produce a hybrid network with excess free volume and nanocrystals uniformly embedded in amorphous matrix. Molecular dynamics simulation and fracture surface analysis further reveal that the hybrid network is able to effectively reduce shear band localization, and therefore delay the fracture of metallic glasses. Graphical abstract: Unlabelled Image Highlights: Electropulsing-assisted surface severe plastic deformation (EP-SSPD) treatment increased plasticity from 0% to 2.03% ± 0.29%. EP-SSPD generated a hybrid structure of 4.1% uniformly-distributed nanocrystals and 0.009% averaged extra free volume. Free volume alleviates localized strain at nanocrystal/matrix interface and nanocrystals retard shear band propagation.